2011
DOI: 10.4061/2011/340763
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Presence of Nasopharyngeal Carcinoma and Marginal Zone (MALT-Type) B-Cell Lymphoma in the Pharynx

Abstract: Synchronous malignancy of squamous cell carcinoma and malignant lymphoma in the head and neck region is extremely rare. Nasopharyngeal carcinoma is a nonlymphomatous, squamous cell carcinoma that occurs in the nasopharyngeal epithelium. Reported herein is a unique case of nasopharyngeal carcinoma occurring simultaneously with MALT-type lymphoma in an 83-year-old woman, who complained of deglutition dysfunction. Endoscopic examination of respective organs revealed a submucosal tumour on the posterior wall of ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Synchronous squamous cell carcinoma in the head and neck region and malignant lymphoma is rare and few have been reported. [24][25][26][27] In our retrospective analysis, 0.04% patients of all malignancies in the head and neck region had synchronous malignant lymphoma. Clinical suspicion of enlarged lymph nodes of the neck is crucial in the differentiation and diagnosis of lymphoma with that of a secondary neck node, so the awareness of this association is crucial for the correct management of this small group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Synchronous squamous cell carcinoma in the head and neck region and malignant lymphoma is rare and few have been reported. [24][25][26][27] In our retrospective analysis, 0.04% patients of all malignancies in the head and neck region had synchronous malignant lymphoma. Clinical suspicion of enlarged lymph nodes of the neck is crucial in the differentiation and diagnosis of lymphoma with that of a secondary neck node, so the awareness of this association is crucial for the correct management of this small group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1). [12–262] The data were extracted from the abstract in 34 articles, [17,37–39,64,75,76,78,81,94,97,103,129,134,151,162,166,170,174,176,192,195,212,221,222,229,232,234,251,252,256,260–262] of which 21 were in English, 5 in Japanese, 3 in Spanish, 2 in French, 2 in Chinese, and 1 in Czech.…”
Section: Resultsmentioning
confidence: 99%
“…According to the previous studies, cases of synchronous lymphoma and other neoplasms in the same organ showed involvement in stomach, thyroid, kidney, throat, and tonsils. [ 10 , 19 21 ] Rare studies have been published on cases showing lymphoma and carcinoma in the lung tissues.…”
Section: Discussionmentioning
confidence: 99%